Verbal vs Nonverbal Cues in Conversation - Dunbar, R (University of Oxford, 2019)
These data were obtained in an online experiment in which they heard 8 audio clips of natural conversations either in English or in (Chilean) Spanish under three conditions (in the order shown): delexicalised, converted to pitch only and full audio. Subjects were asked to identify the relationship between the speakers in each case from a randomised list of 8 relationship types (4 positive/affiliative, 4 negative). The 8 audio clips represent each of these relationship types.